2022
DOI: 10.1123/pes.2021-0075
|View full text |Cite
|
Sign up to set email alerts
|

Physical Literacy of Marginalized Middle School Adolescents in Kansas City Public Schools

Abstract: Purpose: Physical inactivity among adolescents in the United States continues to be a pervasive and growing problem, especially among low income and adolescents of color. Physical literacy is important for adolescents to engage in physical activity. However, few studies have assessed physical literacy among marginalized populations. The purpose of this study is to describe levels of physical literacy among marginalized adolescents in a Midwest City. Methods: Data were collected from 169 participants (85 adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…The results indicated that the physical literacy of young and middle-aged patients with hypertension was at a moderate level, which aligned with the findings of Eighmy et al [ 31 ]. This suggested improvement potential in cognition, emotion, physical competence, and physical activity behavior.…”
Section: Discussionsupporting
confidence: 90%
“…The results indicated that the physical literacy of young and middle-aged patients with hypertension was at a moderate level, which aligned with the findings of Eighmy et al [ 31 ]. This suggested improvement potential in cognition, emotion, physical competence, and physical activity behavior.…”
Section: Discussionsupporting
confidence: 90%
“…In the long term, the adoption of these recommendation may permeate daily practices to achieve a bigger public impact, from high quality in the physical education sector (e.g., early childhood, school age) to effective health promotion (e.g., people of older age and/or chronic diseases). In particular, there is a strong need for PL-related suggestions in older adults [ 46 , 95 ], indigenous people and ethnic minorities [ 96 , 97 ], persons with disabilities [ 31 ], and the general health context [ 98 ]. Depending on the results of the evaluation, PL studies may explicate the message to examine the intervention in new settings or with additional target groups and to systematically test this transfer (horizontal scale-up) [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Schools are an ideal place to promote physical literacy [ 7 ] and physical activity to help students achieve physical activity recommendations [ 8 - 11 ], and physical activity in after-school programming is an effective strategy to increase youth physical activity [ 12 - 14 ]. Programming should focus on developing the foundational skills necessary to participate in a variety of activities, as youth who are more physically literate are more likely to be active throughout life [ 15 ].…”
Section: Introductionmentioning
confidence: 99%